Guidelines adherence and hypertension control at a tertiary hospital in Malaysia. Issue 5 (15th May 2012) - Ahmad, Nafees; Hassan, Yahaya; Tangiisuran, Balamurugan; Meng, Ong Loke; Aziz, Noorizan Abd; Ahmad, Fiaz‐ud‐Din; Atif, Muhammad
Abstract: Rationale, aims and objectives  Existing literature suggests that doctors' poor adherence with guidelines is one of the major contributing factors to suboptimal control of hypertension. This study aims to evaluate doctors' adherence with Malaysian clinical practice guideline (CPG 2008) in a tertiary care hospital, and factors associated with guideline adherence and hypertension control. Methods  This was a cross‐sectional study conducted at Hospital Pulau Pinang, Penang, Malaysia. Prescriptions written by 26 enrolled doctors to 650 established hypertensive outpatients (25 prescriptions per enrolled doctor) were noted on visit 1 along with patients' demographic and clinical data. The noted prescriptions were classified either as compliant or non‐compliant to CPG (2008). Five hundred twenty (80%) of the enrolled patients (20 patients per enrolled doctor) were followed for one more visit. Blood pressure (BP) noted on visit 2 was related to the prescription written on visit 1. SPSS 16 (SPSS Inc., Chicago, IL, USA) was used for data analysis. Results  Three hundred forty‐nine (67.1%) patients received guidelines compliant pharmacotherapy. In multivariate analysis, hypertension clinic had significant negative association with guidelines adherence. Two hundred sixty‐five patients (51%) were at goal BP on visit 2. In multivariate analysis, angiotensin‐converting enzyme inhibitors and guidelines adherence had significant positive, while renal disease, diabetes mellitus and diabetic clinic had significant negative association with hypertension control. Conclusions  An overall fair level of adherence with guidelines and better control of hypertension was observed. Guidelines compliant practices resulted in better control of hypertension. The gaps between what guidelines recommend and clinical practice were especially seen in the pharmacotherapy of uncomplicated hypertension and hypertension with diabetes mellitus and renal disease.